Hubungan Tingkat Pengetahuan Remaja Tentang HIV/AIDS dengan Perilaku Seksual Remaja Siswa Kelas X dan XI di SMKN 1 Babelan – Bekasi - Santika, Santika; Yuliani, Indah (Universitas Malahayati, 2023)
ABSTRACT A virus known as the human immune deficiency virus (HIV) targets the human immune system. HIV attacks the human body by killing or destroying cells of the immune system, drastically reducing the body's resistance to infection and cancer. Acquired immune deficiency syndrome (AIDS) is a group of symptoms caused by a damaged immune system. This disease does not come from birth. Instead, it was passed from person to person. To determine the relationship between the level of knowledge of adolescents about HIV/AIDS and the sexual behavior of adolescents in grades X and XI at SMKN 1 Babelan. This research using a descriptive-correlative research design aims to determine the relationship between adolescent sexual behavior and the level of knowledge of adolescents about HIV/AIDS. Cross-sectional data collection was used in this study, which was carried out simultaneously with a total sample of 96 respondents. it can be seen that 30 students (65.2%) have a poor level of knowledge about HIV/Helps and 31 students (62%) who have a good level of knowledge about HIV/AIDS have a way of behaving. who do not respect adolescent sexuality. The calculated p-value is 0.908, higher than the calculated value of = 0.05. It can be concluded that there is no significant relationship between the level of knowledge of adolescents about HIV/AIDS and their sexual behavior. Keywords: Knowledge, HIV/AIDS, Adolescent Sexual Behavior ABSTRAK Virus yang dikenal sebagai human immune deficiency virus (HIV) menargetkan sistem kekebalan tubuh manusia. HIV menyerang tubuh manusia dengan membunuh atau menghancurkan sel-sel sistem kekebalan tubuh, mengurangi daya tahan tubuh terhadap infeksi dan kanker secara drastis. Acquired immune deficiency syndrome (AIDS) adalah sekelompok gejala yang disebabkan oleh rusaknya sistem kekebalan tubuh. Penyakit ini tidak datang sejak lahir. Sebaliknya, itu ditularkan dari orang ke orang. Untuk mengetahui hubungan tingkat pengetahuan remaja tentang HIV/AIDS dengan perilaku seksual remaja siswa kelas X dan XI di SMKN 1 Babelan. Penelitian yang menggunakan desain penelitian deskriptif korelatif ini bertujuan untuk mengetahui hubungan antara perilaku seksual remaja dengan tingkat pengetahuan HIV/AIDS remaja. Pengumpulan data cross-sectional digunakan dalam penelitian ini, yang dilakukan secara bersamaan dengan jumlah sampel sebanyak 96 responden. dilihat bahwa 30 siswa (65,2%) memiliki tingkat pengetahuan yang kurang baik tentang HIV/AIDS dan 31 siswa (62%) yang memiliki tingkat pengetahuan yang baik tentang HIV/AIDS memiliki cara berperilaku yang tidak menjunjung tinggi seksualitas remaja. Nilai p yang dihitung adalah 0,908, lebih tinggi dari nilai yang dihitung dengan = 0,05. Dapat disimpulkan bahwa tidak terdapat hubungan yang signifikan antara tingkat pengetahuan remaja tentang HIV/AIDS dengan perilaku seksualnya. Kata Kunci : Pengetahuan, HIV/AIDS, Perilaku Seksual Remaja